The Correlation Between Mother's Knowledge about Complementary Feeding with The Incidence of Stunting in Toddlers Under Two in Mayang, Jember - Dwita Aryadina Rachmawati; Ranindya Putri Cipta Indraswari; Elly Nurus Sakinah (Journal of Agromedicine and Medical Sciences, 2022)
Stunting is a condition of toddlers who have a height-for-age less than -2 SD WHO Z-score. The period from a newborn until two years is also known as the golden period. Nutrition obtained after birth affects the growth and development of them. Complementary feeding was given when they were 6 months old. The level of mother's knowledge about complementary foods has an impact on complementary feeding. Inappropriate complementary feeding can lead to stunting. The research objective was to determine the correlation between mother's knowledge about complementary feeding and the incidence of stunting in toddlers under two in Mayang. The research was an analytical observational with a cross sectional study design. The sample was 90 respondents taken using consecutive sampling method. Data collection using a questionnaire on the mother and using height-for-age data from the toddlers. Statistical test using the Spearman test, showed that there was a significant correlation between the level of mother's knowledge about complementary feeding and the incidence of stunting (p=0.024.; rho=-0.238). Due to this result, we recommend continuous health promotion and education among mothers to decrease the risk of stunting in their children. Keywords: stunting, complementary feeding, toddlers under two, mother’s knowledge